2021
DOI: 10.1200/po.20.00439
|View full text |Cite
|
Sign up to set email alerts
|

Ceralasertib-Mediated ATR Inhibition Combined With Olaparib in Advanced Cancers Harboring DNA Damage Response and Repair Alterations (Olaparib Combinations)

Abstract: PURPOSE Poly (ADP-ribose) polymerase (PARP) inhibitors have emerged as promising therapy in cancers with homologous recombination repair deficiency. However, efficacy is limited by both intrinsic and acquired resistance. The Olaparib Combinations basket trial explored olaparib alone and in combination with other homologous recombination–directed targeted therapies. Here, we report the results of the arm in which olaparib was combined with the orally bioavailable ataxia telangiectasia and RAD3-related inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…DDR inhibitors are reported to be very active in combination treatments, in vitro and in vivo ovarian cancer models [ 43 ], and in some cases can overcome PARPi resistance (for a recent review see [ 44 , 45 ]). Indeed, early clinical trials of PARPi combined with Wee1, Chk1 and ATR inhibitors have been explored in different subsets of OC patients [ 46 , 47 , 48 , 49 , 50 ]. We tested the combination of Wee1, Chk1 and ATR inhibitors with olaparib in our models ( Figure 5 and Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…DDR inhibitors are reported to be very active in combination treatments, in vitro and in vivo ovarian cancer models [ 43 ], and in some cases can overcome PARPi resistance (for a recent review see [ 44 , 45 ]). Indeed, early clinical trials of PARPi combined with Wee1, Chk1 and ATR inhibitors have been explored in different subsets of OC patients [ 46 , 47 , 48 , 49 , 50 ]. We tested the combination of Wee1, Chk1 and ATR inhibitors with olaparib in our models ( Figure 5 and Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…A phase I trial combining the AKT inhibitor capivasertib with olaparib revealed durable responses in patients with advanced-stage solid tumors, irrespective of BRCA1/2 status [59]. Another study showed a potential clinical activity with manageable toxicity with ceralasertib, an AKT inhibitor, in combination with olaparib in BRCA-mutated PARPi-resistant HGSOC, with a duration of benefit that exceeded the duration achieved on prior PARPi monotherapy [60,61].…”
Section: Indirect Inhibition Of Hrmentioning
confidence: 99%
“…Even though these drugs display similar toxicities, preliminary data suggest that they can be combined safely, adopting dose and schedule adjustments [ 130 ]. The association of olaparib and ceralasertib seems to be better tolerated compared to olaparib and prexasertib, especially in terms of hematological toxicities [ 131 , 132 , 133 ]. However, additional studies are necessary, even in this case, to clarify the safety profile of these combinations.…”
Section: Combination Regimensmentioning
confidence: 99%